2021
DOI: 10.3390/genes12111688
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Plant Heterosis—From Field Scale to Molecules

Abstract: Heterosis refers to the increase in biomass, stature, fertility, and other characters that impart superior performance to the F1 progeny over genetically diverged parents. The manifestation of heterosis brought an economic revolution to the agricultural production and seed sector in the last few decades. Initially, the idea was exploited in cross-pollinated plants, but eventually acquired serious attention in self-pollinated crops as well. Regardless of harvesting the benefits of heterosis, a century-long disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…Results in Table 4a and b reflecting that dominance plays greater role in inheritance of most studied traits, so selection for improvement these traits could be effective in late generations. Additive x additive gene effect was more effective than dominance x dominance and additive x dominance reflecting the important of this type of gene action, similar results were obtained by Mansour [22], Andreia et al [24] and Attiq et al [21]. Bojan et al [28] reported that, dominant was more important than additive component.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results in Table 4a and b reflecting that dominance plays greater role in inheritance of most studied traits, so selection for improvement these traits could be effective in late generations. Additive x additive gene effect was more effective than dominance x dominance and additive x dominance reflecting the important of this type of gene action, similar results were obtained by Mansour [22], Andreia et al [24] and Attiq et al [21]. Bojan et al [28] reported that, dominant was more important than additive component.…”
Section: Discussionsupporting
confidence: 72%
“…The increase in biomass, fertility, stature and other characters that led to desirable performance of the F 1 progeny compared to parents refers to heterosis [21]. For variety evolution as well, selection of better combination heterosis role cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The illustration shows closely related pairs of sister taxa in which one is predominantly self-pollinating (taxa name in green) and the other is cross-pollinating (taxa name in blue). The predominantly self-pollinating species, namely, Arabidopsis ( Klosinska et al, 2016 ), Gossypium ( Rehman et al, 2021 ), Hordeum ( Guo et al, 2018 ), and Triticum ( Qiu et al, 2017 ) show high epigenetic marks. The phylogenetic background is drawn to show the relative systematic positions.…”
Section: Underpinning Of Epigenetic Adaptive Responses In Natural Pop...mentioning
confidence: 99%
“…He further indicated that a combination of various mechanisms produced heterosis in complex traits. Rehman et al (2021) reviewed various studies on heterosis and pointed out that increased knowledge across fields of science, such as genetics, epigenetics, genomics, proteomics, and metabolomics, provided new insights into understanding the expression of hybrid vigor or heterosis.…”
Section: Introductionmentioning
confidence: 99%